помогите решить: 4 х (х-1) — (2 х +5) (2 х-5)=1;…

Тема в разделе "Алгебра", создана пользователем Screamer89, 17 апр 2020.

  1. Screamer89

    Screamer89 Мелюзга

    Регистрация:
    21 ноя 2014
    Сообщения:
    0
    Симпатии:
    0
    помогите решить: 4 х (х-1) — (2 х +5) (2 х-5)=1; 3 х-5 (х +1) (х-1)+5 (х +2) (х-2)=6; 3 (2 х +1) (2 х-1) -4 (3 х-2) (3 х +2)+6 х (4 х +1)=31?
     
  2. Marker1

    Marker1 Мелюзга

    Регистрация:
    7 июн 2013
    Сообщения:
    0
    Симпатии:
    0
    1) 4 х (х-1) — (2 х +5) (2 х-5)=14 х^2-4 х-4 х^2+10 х-10 х +25=1-4 х +25=14 х=25-14 х=24 х=24/4 х=6 Проверка: 4*6 (6-1) — (2*6+5) (2*6-5)=124*5- (12+5) (12-5)=124*5- (12*12-12*5+5*12-5*5)=1120- (144-60+60-25)=1120-144+60-60+25=1120+25-144=1145-144=11=1 2) 3 х-5 (х +1) (х-1)+5 (х +2) (х-2)=63 х-5 (х^2-х + х-1)+5 (х^2-2 х +2 х-4)=63 х-5 (х^2-1)+5 (х^2-4)=63 х-5 х^2+5+5 х^2-20=63 х=6+20-53 х=21 х=7 Проверка: 3*7-5 (7+1) (7-1)+5 (7+2) (7-2)=621-5*(49-1)+5 (49-4)=621-5*48+5*45=621-240+225=6246-240=66=6 3) 3 (2 х +1) (2 х-1) -4 (3 х-2) (3 х +2)+6 х (4 х +1)=313 (4 х^2-1) -4 (9 х^2-4)+24 х^2+6 х=3112 х^2-3-36 х^2+16+24 х^2+6 х=316 х=31+3-166 х=18 х=18/6 х=3 Проверка: 3 (2*3+1) (2*3-1) -4 (3*3-2) (3*3+2)+6*3 (4*3+1)=313 (6+1) (6-1) -4 (9-2) (9+2)+18*13=313*35-4*77+234=31105-308+234=3131=31
     

Поделиться этой страницей